The Influence of Self-efficacy on Resilience in Students Who Work in Thesis - Adelana Tesalonika Riswantyo; Krishervina Rani Lidiawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2021)
Students who are working on their final project often faced with various problems and pressures. They need to build self-efficacy to be able to increase confidence in achieving something. Self-efficacy is an individual’s belief in their ability to organize and take steps in solving certain problems or tasks. Individuals with high self-efficacy view difficult tasks as challenges to face rather than as threats to avoid. Respondents are highly committed to achieving its goals, respondents will also invest a high level of effort and strategic thinking to deal with failure. Resilience is the ability to thrive in the face of adversity in every individual whilst facing problems or pressure. By increasing resilience, humans can develop life skills such as communicating, realistic abilities in making life plans, and being able to take the right steps for their lives. This study was conducted to determine whether self-efficacy has an effect on resilience. The research design used in this study is a quantitative research design with a sample of 75 people and the population of this study is students who are working on a thesis. The data were first analysed for validity, reliability, and followed by simple regression analysis. The results showed that self-efficacy had an effect on the resilience of 30,5% and a significant value of p = .000 (p<0.05), testing the effect of the dimensions of self-efficacy on resilience showed results that strength has the greatest influence on resilience.